2017
DOI: 10.3390/nu9080910
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Healthy Eating Index 2010 for the Canadian Population: Evidence from the Canadian Community Health Survey

Abstract: The Healthy Eating Index (HEI) is a diet quality index shown to be associated with reduced chronic disease risk. Older versions of the HEI have been adapted for Canadian populations; however, no Canadian modification of the Healthy Eating Index-2010 (HEI-2010) has been made. The aims of this study were: (a) to develop a Canadian adaptation of the HEI-2010 (i.e., Healthy Eating Index-Canada 2010 (HEI-C 2010)) by adapting the recommendations of the HEI-2010 to Canada’s Food Guide (CFG) 2007; (b) to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 34 publications
2
28
1
2
Order By: Relevance
“…Our study was in agreement with Jessri et al [10] who reported that, HEI is diet quality index which measure diet quality and associated with decreased risk of chronic disease. HEI-score showed significant positive correlation with prevalence and incidence of anemia as children who intake healthy foods (contain essential nutrients) had good HEI-score and decreased risk of their anemia…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study was in agreement with Jessri et al [10] who reported that, HEI is diet quality index which measure diet quality and associated with decreased risk of chronic disease. HEI-score showed significant positive correlation with prevalence and incidence of anemia as children who intake healthy foods (contain essential nutrients) had good HEI-score and decreased risk of their anemia…”
Section: Discussionsupporting
confidence: 93%
“…Higher HEI-scores indicate the consumption of healthy foods and detect eating behaviors [9]. The risk of chronic disease decreased after using HEI as an index of diet quality (Table 1) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Updated evidence based on consumption of nutrients to limit and on adherence to the recently released 2019 Canada's Food Guide are warranted to assess the progress towards achieving the WHO "best buy" policies [22]. Results from this study provide such evidence for Canadians, and can be used to improve the nutritional quality of the food supply and develop targeted policies supporting healthier food choices for the population [6,7,15,16,[30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…A diet quality score was specifically developed for the Atlantic PATH study using criteria adapted from the US and Canadian HEI (HEI-C) [29,30] as not all information was available to construct the HEI-C. Details of the Atlantic PATH diet quality score derivation have been previously published [27].…”
Section: Dietary Intakementioning
confidence: 99%